Among 69,178 UK Residents Ages 65+ Years, Frailty Associates Significantly With Lifestyle Behaviors and Depression: A Cross‐Sectional Study - Jisu Kim; Jonathan Kenyon; Juan Lu; Lana Sargent; Youngdeok Kim (Health Science Reports)
ABSTRACT Background Frailty and depression are highly prevalent in older adults. However, the complex association of their interlinked factors, including lifestyle behaviors, remains unexplored in population‐based epidemiological studies. Aims This study aimed to evaluate the relationship between frailty and depression and to determine associated modifiable lifestyle risk factors for depression among older adults in the UK Biobank (UKB). Methods Data were obtained from 69,178 older adults (aged ≥ 65 yrs) in the baseline survey of the UKB. Frailty status was measured using the frailty phenotype criteria (range: 0–5). Participants were classified into frail (≥ 3), pre‐frail (1–2), and non‐frail (0) groups. The outcome of depression was defined by participants who had sought medical attention for nerves, anxiety, tension, or depression. Lifestyle behaviors included the self‐reported time spent in moderate‐to‐vigorous physical activity (MVPA), screen‐based sedentary behavior, and sleep. The association of interest is examined using multivariable logistic regression models. Results 29% of participants had depression, of which 7% and 45% were frail and pre‐frail, respectively. Significant correlations are observed between frailty and lifestyle behaviors (p's < 0.05). Frailty is significantly associated with increased odds of having depression (Frail: aOR = 1.87, 95% CI = 1.72, 2.04); Pre‐frail: aOR = 1.22, 95% CI = 1.18, 1.27), and sleep (7–8 h/d) is associated with lower odds of having depression (aOR = 0.81, 95% CI = 0.78, 0.84). Conclusion Frail and pre‐frail older adults have a higher likelihood of experiencing depression than their non‐frail counterparts. Meeting the recommended sleep duration (7–8 h/d) can be used as a modifiable behavioral strategy to manage or prevent depression. Further longitudinal studies are warranted to examine the time sequence in this relationship.